Indirect Tax: Trend and Structure in Nepal - Dangal, Dil Nath (Humanities and Social Sciences Journal, 2021)
This study tries to analyze the trend and structure of indirect tax in Nepal and examine the contribution of indirect tax in Gross Domestic Product of Nepal. This study has been based on secondary data published by the Government of Nepal covering a period between 2002/03 to 2019/20 fiscal year. Descriptive method of analysis has been adopted in the study. During the study period, the percentage contribution of indirect taxes to Gross Domestic Product ranges from 6.60 to 14.45. The percentage contribution is observed to be increasing along with the fluctuation trend till 2018/19 but decreased in 2019/20 as compared to earlier years.